Retraction notice to “Green and rapid and instrumental one-pot method for the synthesis of imidazolines having potential anti-SARS-CoV-2 main protease activity” [Sustain. Chem. Pharm. 34 (2023) 101136] - Sabikeh Azimi; Muna S. Merza; Fatemeh Ghasemi; Hasan Ali Dhahi; Farid Baradarbarjastehbaf; Mehdi Moosavi; Pouya Ghamari Kargar; Christophe Len (Sustainable Chemistry and Pharmacy, 2025)

Diminishing benefits of thermal mass in Iranian climate: Present and future scenarios - Eugénio Rodrigues; Nazanin Azimi Fereidani; Marco S. Fernandes; Adélio R. Gaspar (Building and Environment, 2024)

Identifying snowfall elevation patterns by assimilating satellite-based snow depth retrievals - Manuela Girotto; Giuseppe Formetta; Shima Azimi; Claire Bachand; Marianne Cowherd; Gabrielle De Lannoy; Hans Lievens; Sara Modanesi; Mark S. Raleigh; Riccardo Rigon; Christian Massari (Science of The Total Environment, 2024)

RETRACTED: Green and rapid and instrumental one-pot method for the synthesis of imidazolines having potential anti-SARS-CoV-2 main protease activity - Sabikeh Azimi; Muna S. Merza; Fatemeh Ghasemi; Hasan Ali Dhahi; Farid Baradarbarjastehbaf; Mehdi Moosavi; Pouya Ghamari Kargar; Christophe Len (Sustainable Chemistry and Pharmacy, 2023)

A novel tissue culture model for evaluating the effect of aging on stem cell fate in adult microvascular networks - Mohammad S. Azimi; Jessica M. Motherwell; Maria Dutreil; Ryan L. Fishel; Matthew Nice; Nicholas A. Hodges; Bruce A. Bunnell; Adam Katz; Walter L. Murfee (GeroScience, 2020)

Transplantation of Directly Reprogrammed Human Neural Precursor Cells Following Stroke Promotes Synaptogenesis and Functional Recovery - Ilan Vonderwalde; Ashkan Azimi; Gabrielle Rolvink; Jan-Eric Ahlfors; Molly S. Shoichet; Cindi M. Morshead (Translational Stroke Research, 2020)

Correction to: Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)
The article Microbial Exchange via Fomites and Implications for Human Health, written by Brent Stephens, Parham Azimi, Megan S. Thoemmes, Mohammad Heidarinejad, Joseph G. Allen, and Jack A. Gilbert, was originally published electronically on the publisher’s internet portal

Microbial Exchange via Fomites and Implications for Human Health - Brent Stephens; Parham Azimi; Megan S. Thoemmes; Mohammad Heidarinejad; Joseph G. Allen; Jack A. Gilbert (Current Pollution Reports, 2019)

Analysis of drought recurrence conditions using first-order reliability method - S. Azimi; M. Azhdary Moghaddam; S. A. Hashemi Monfared (International Journal of Environmental Science and Technology, 2019)

Simultaneous sulfamethoxazole and trimethoprim removal and biofilm growth characteristics in attached growth bioreactor - N. Azimi; G. D. Najafpour; A. H. Hassani; S. M. Borghei (International Journal of Environmental Science and Technology, 2018)

Phylogeny and divergence times of the Coluteoid clade with special reference to Colutea (Fabaceae) inferred from nrDNA ITS and two cpDNAs, mat K and rpl 32- trn L (UAG) sequences data - M. Moghaddam; S. Kazempour Osaloo; H. Hosseiny; F. Azimi (Plant Biosystems, 2017)

Artificial neural network coupled with wavelet transform for estimating snow water equivalent using passive microwave data - A B Dariane; S Azimi; A Zakerinejad (Journal of Earth System Science, 2014)